Safety and efficacy of ipilimumab to treat advanced melanoma in the setting of liver transplantation. Issue 1 (16th June 2015) - Morales, Rita E; Shoushtari, Alexander N; Walsh, Michelle M; Grewal, Priya; Lipson, Evan J; Carvajal, Richard D
Abstract : Ipilimumab is a first-in-class immunological checkpoint blockade agent and monoclonal antibody against Cytotoxic T-Lymphocyte Antigen 4 (CTLA-4) that has demonstrated survival benefit and durable responses in patients with metastatic melanoma. To date, solid organ transplant recipients have been excluded from clinical trials with cancer immunotherapies on the basis of their concurrent treatment with immunosuppressive agents. We present the first case to our knowledge of a patient with advanced cutaneous melanoma receiving ipilimumab status post orthotopic liver transplantation with a partial response. Transaminitis was observed 4 months after administration of ipilimumab that resolved with close observation. No evidence of graft rejection has been observed to date. This case advocates for further investigation of the safety and efficacy of cancer immunotherapies in solid organ transplant recipients.